Optimasi Formula Gel Ekstrak Buah Mengkudu (Morinda Citrifolia L.) Sebagai Antioksidan Dengan Metode Simplex Lattice Design - Dewi Ekowati; Evie Yuliaswari; Endang Sri Rejeki (Jurnal Farmasi Indonesia, 2016)
Noni Fruit (Morinda citrifolia L.) contains polyphenols, flavonoids, saponins, which plays a role as an antioxidant. Noni fruit extract is formulated in gel dosage form for the comfortness and convenience of topical use. This research aims to obtain the optimum formula noni fruit gel which effective as an antioxidant. Gel formula was optimazed by method of Simplex Lattice Design (SLD). design-expert 8.0.6.1. Gel formula was preparated using CMC-Na base (A) and (B) Carbopol 940 so it was obtained 3 formula, i.e. F1 (100% A:0% B), F2 (50% A:50% B), F3 (0% A:100% B) and then was optimized based on physical properties of viscosity, adhesivity, power spread and the shift of viscosity. The SLD's equation was used to make the gel with the response a total of physical prop erties of the gel the most optimum. Optimum gel tested antioxidant activity by using DPPHmethod. Antioxidant activity the ï¬ maximum and operating time so the IC50 values were obtained through analysis of probit with the use of vitamin C as a comparison. The optimum formula of noni fruit extract gel obtained by SLD method was the formula contained CMC-Na 78,92% : carbopol 940 21,08% with the desirability value of 0,511. The t-test results of viscosity, power latched onto, power spread and the shift of viscosity shows no significant difference. The results demonstrated the optimum gel fruit noni had antioxidant activity with IC50 value of 92,875 ppm.